Gestational Diabetes Mellitus (GDM) and Autism Risk in Offspring: A Systematic Review and Meta-Analysis - Laksmy Dewi Sukmakarti; Arif Siswanto (Poltekkes Kemenkes Surakarta, 2025)
Background: Autism spectrum disorder (ASD) affects social communication and reciprocal interaction abilities in children. Maternal diabetes mellitus during pregnancy, specifically gestational diabetes mellitus (GDM), represents a potentially modifiable risk factor associated with elevated ASD risk in offspring. The aim of this study was to assess the relationship between diabetes in mothers and the risk of autism spectrum disorder (ASD) in children through a systematic review and meta-analysis. Methods: This research is a systematic review and meta-analysis of nine cohort studies involving diverse populations to evaluate the association between mothers with diabetes during pregnancy and the risk of ASD in their offspring (2015–2024) sourced from PubMed, Google Scholar, and ScienceDirect. A random-effects model was used to calculate adjusted odds ratios (aOR). Results: Data from 3,908,133 children showed that maternal diabetes increases the ASD risk by 16% (aOR = 1.16, 95% CI: 1.11–1.22, p<0.001), with significant heterogeneity (I² = 79%). Conclusion: This meta-analysis identified a statistically significant but modest association between maternal diabetes mellitus during pregnancy and ASD risk in offspring. The relationship reflects an observational association and cannot establish causality. These findings emphasize the clinical importance of preconception glycemic optimization, enhanced antenatal monitoring of maternal glucose control, and developmental surveillance of offspring born to diabetic mothers.